Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

I have shown that the power series $$\sum\limits_{i=1}^\infty \frac{x^n}{n^2} = -\int\limits_{0}^x \frac{\log(1-t)}{t}dt$$ for $x\in (-1,1)$. How can I show that this is also true for the boundary: $$\sum\limits_{k=1}^\infty \frac{1}{n^2}=-\int\limits_{0}^1 \frac{\log(1-t)}{t}dt$$

I hope somebody can help :)

Best regards

share|cite|improve this question
You are making a tacit use of Abel's theorem. – ncmathsadist May 22 '12 at 17:59
up vote 1 down vote accepted

I assume this is what you did



$$-\frac{\log(1-x)} x=\sum_{n=1}^{\infty}\frac{x^{n-1}}{n}$$

The series is clearly valid for $[-1,1)$, since for $x=-1$ we get the alternating harmonic series, which converges to $\log 2$. We now integrate termwise in the interval $(0,x)$, getting

$$-\int_0^x\frac{\log(1-t)} tdt=\sum_{n=1}^{\infty}\frac{x^{n}}{n^2}$$

What happens if we let $x=1$?

$$-\int_0^1\frac{\log(1-t)} tdt=\sum_{n=1}^{\infty}\frac{1}{n^2}$$

The series converges and is $\dfrac{\pi^2}{6}$, so the integral can be assigned this value. You can also try changing some variables to get a "nicer" integral:

$$1 - t = {e^{ - h}}$$

$$\int_0^\infty {\frac{h}{{{e^h} - 1}}} dh$$

When $h \to \infty$ the integral goes rapidly to $0$, and when $h \to 0$ the integral goes to $1$, so there is no "bad" singularity to worry about.

share|cite|improve this answer

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.